2017
DOI: 10.2501/ijmr-2017-004
|View full text |Cite
|
Sign up to set email alerts
|

How Political Candidates' Use of Facebook Relates to the Election Outcomes

Abstract: This paper examines the relationship between political candidates' use of Facebook and their election outcomes (vote share and election success). The use of social media in political marketing campaigns has grown dramatically over the past few years. It is also expected to become even more critical to future political campaigns, as it creates two-way communication and engagement that stimulates and fosters candidates' relationships with their supporters. Online Facebook data were acquired for all 84 candidates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 26 publications
1
21
0
6
Order By: Relevance
“…Apart Person playing the most number of roles V2565 (38450 roles) V2565 (73900 roles) V2565 (37508 roles) V2565 (68624 roles) from these results, research community has also shown that contacts and actions of those contacts of an individual, influence her/his participation and decision-making process respectively in voting on Wikipedia (Lee et al 2012). Furthermore, our results also seems consistant with the findings of (Lin 2017) and (Spierings and Jacobs 2014) about the importance of contacts of a candidate in electoral outcome on other OSNs e.g. Facebook and Twitter.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Apart Person playing the most number of roles V2565 (38450 roles) V2565 (73900 roles) V2565 (37508 roles) V2565 (68624 roles) from these results, research community has also shown that contacts and actions of those contacts of an individual, influence her/his participation and decision-making process respectively in voting on Wikipedia (Lee et al 2012). Furthermore, our results also seems consistant with the findings of (Lin 2017) and (Spierings and Jacobs 2014) about the importance of contacts of a candidate in electoral outcome on other OSNs e.g. Facebook and Twitter.…”
Section: Discussionsupporting
confidence: 87%
“…It is explored that importance of contacts of a candidate in terms of number of fans of a candidate on the Facebook in municipal election carried out in Taiwan. It is found that number of online fans of a candidate is positively associated to the election outcomes (Lin 2017). It has been examined, that the number of followers of a candidate positively contributes towards preferential voting against him, provided that candidate is actively participating in OSNs (Spierings and Jacobs 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Although it is widely thought that Social Networks have a decisive influence on election campaigns, there seems to be no clear evidence that the use of Twitter and Facebook leads to success in elections. Some scholars identify correlations (Livne et al, 2011;LaMarre & Suzuki-Lambrecht, 2013;Gomez, 2014;Lin, 2017) but most scholars deny them (Vergeer et al, 2011;Strandberg, 2013;Huberty, 2015;Miller Noah & Ko Rosa, 2015;Murthy, 2015;Prémont & Millette, 2015;McGregor et al, 2017). Similarly, scholars are divided on the link between the popularity of candidates and political parties on Social Networks and electoral victory.…”
Section: The Effects Of Social Networkmentioning
confidence: 99%
“…The 2‐minute stump speech expressing the candidate's key focus is used throughout the campaign in all types of settings. With the increasing prominence of social media, it is helpful to have one team member whose job is to optimize constituent support and commitment through this fast and effective type of communication using vivid, interactive posts that build connection and relationships . A prominent social media presence has been shown to increase the odds of winning elections.…”
Section: Getting the Message Outmentioning
confidence: 99%